Bridging Banking and Education: Evaluating the Multifunctional Use of the Tertiary Education Student ATM Card - Adeleye, Jeremiah Adedamola; Alaba, Famuyide Johnson; Abosede, Adesanya Bukunola; Gbeleyi, Olasunkanmi; Olusegun, Oguntade Paul (Journal of Educational Sciences, 2025)
To enhance student services and promote financial inclusion, Lagos State University (LASU), in collaboration with Lotus Bank, introduced a multifunctional identity card that integrates student identification with banking features and Near Field Communication (NFC) capabilities. This study evaluates the usability, adoption, and effectiveness of the LASU Student ATM ID card among the student population. The study was carried out among LASU students and a multistaged sampling techniques were adopted for the study. A descriptive survey design was adopted, and data were collected using a structured questionnaire administered to undergraduate students who had received the card. Five research questions were formulated and were interpreted. The findings revealed that the ATM ID card was widely accepted and used as a means of identification within some areas in the school but not being used in library, health centres, NFC portion of the card was not known to most of the students. Challenges identified include low awareness, and insufficient integration with university systems such as automated attendance. The study concludes by recommending enhancements to the card’s functionality, including improved awareness campaigns, better NFC integration within the university, and expansion of use cases within the campus environment.